Cleanup of atrazine-contaminated soils: ecotoxicological study on the efficacy of a bioremediation tool with Pseudomonas sp. ADP - Chelinho, Sónia (2020)
Purpose To mitigate the environmental effects of atrazine, one of the cleanup strategies available is based on the use of atrazine-degrading bacteria. This work aimed to evaluate the efficacy of a previously developed bioremediation tool for atrazine-contaminated soils (combining bioaugmentation with Pseudomonas sp. ADP, hereafter designated as P. ADP, and biostimulation with citrate) on both soil habitat and retention functions, by performing ecotoxicological tests with standard soil and aquatic species. Materials and methods Soil microcosms (incorporating earthworms, collembolans, and plants) were spiked with three doses of Atrazerba FL, an atrazine commercial formulation: the recommended dose (RD; 2 L/ha), 10×RD and 20×RD to simulate overuse/accidental spills scenarios. The experiment included two main groups of treatments: (1) microcosms sprayed solely with Atrazerba, i.e., nonbioremediated soils (NB) and (2) microcosms sprayed with both Atrazerba and the bioremediation tool (addition of P. ADP plus citrate), i.e., bioremediated soils (B). Control microcosms with no herbicide or P. ADP plus citrate addition were also set up. Besides soil chemical analysis, the following ecotoxicological endpoints were assessed to monitor bioremediation: plant biomass production, earthworm reproduction, microalgae growth (in eluates— collected 5 and 10 days after the bioremediation treatment— and leachates—collected on day seven), and cladoceran reproduction (in soil eluates). Results In NB soils, all Atrazerba doses induced a severe reduction in plant biomass production, and no effects were found for earthworm’s reproduction. Eluates and leachates obtained from the NB soils caused deleterious effects on both microalgae growth and cladoceran reproduction. Chemical analysis showed that atrazine degradation was faster in B soils than in the correspondent NB soils. Data from toxicity tests indicated that test organism performance was enhanced in B soils and respective eluates and leachates, compared to the NB samples. In fact, for soils contaminated with 10 and 20×RD Atrazerba doses, plant biomass production was significantly higher in the B soils than in the correspondent NB soils. Regarding the effects of soil bioremediation on the toxicity of soil eluates and leachates, for the soil contaminated with 10×RD of Atrazerba, over a 5-day treatment period, both microalgae growth and cladoceran reproduction were significantly higher in water extracts obtained from the B soils when compared with the NB extracts and also similar to the control. By the contrary, for the highest Atrazerba dose tested (20×RD), no significant differences were found on the toxicity of B and NB eluates toward both aquatic test organisms. However, for this same dose, after 7 days, microalgae growth was higher in B than in the NB leachates and similar to the control. Yet, after a longer bioremediation period of 10 days, eluates were also no longer toxic to both aquatic organisms. Discussion Based on atrazine soil chemical analysis, one can state that the addition of P. ADP plus citrate to the atrazine-contaminated soils was clearly effective in promoting atrazine biodegradation. In addition, ecotoxicological data support the efficacy of this cleanup tool. Indeed, results showed that the bioremediation treatment resulted in a relevant reduction on soil toxicity to a plant (approximately 100% and 72% of control, respectively, for 10× RD and 20×RD contaminated soils). In addition, 5 days of P. ADP activity were enough to annul atrazine toxic effects toward microalgae and cladocerans in eluates obtained from the soil contaminated with 10×RD of Atrazerba. For 20×RD, an effective detoxification of eluates was achieved only after a longer bioremediation period of 10 days. Conclusions The ecotoxicity tests proved not only the effective detoxification of bioremediated soils in 10 days but also the potential ability to concurrently reduce atrazine contamination of water compartments due to leaching and/ or run-off events, to levels that may no longer be hazardous to ecosystems. Due to the worldwide continued use of atrazine/triazine-based herbicidal formulations, further studies viewing the optimization of this cost-effective cleanup tool at larger scales (mesocosm and real field scenarios) and testing of other commercial formulations containing mixtures of atrazine/triazine and other active ingredient are still needed so that bioremediation can be used as a valuable tool to reduce herbicide toxicity in contaminated land.